Managing English culture in semi-military academy - Yusi Rahmawati; Agus Pamungkas Rismilia Putra; Priyanto Priyanto; Iik Suryanti Azizah; Sulida Erliyana; Aan Rubiyanto (Universitas Aki, 2024)
The efficient administration of English culture in semi-military academies becomes a substantial area to cover as long as these institutions remain major players in molding future leaders. This research looks at the difficulties, approaches, and results of maintaining English culture in the special setting of a semi-military institution. Language hurdles, cultural misinterpretations, and difficulties between academic independence and military discipline are only a few of the difficulties that are shown by the findings. To promote cultural diversity and strengthen institutional cohesiveness, cutting-edge tactics, including inclusive curriculum design, bilingual programs, and cultural competency training, have been recognized as crucial. The survey also emphasizes the perceived benefits of successful English cultural management, which include better performance in school, better interpersonal abilities, and a stronger feeling of community among students and staff. This study provides theoretical insights into the dynamic interactions between culture, education, and institutional identity by drawing on theories of cultural management, education, and organizational behavior. Moreover, it offers useful suggestions for teachers, administrators, and legislators who want to encourage inclusivity and diversity of culture in semi-military academies and other similar educational environments.